Development of Ecotourism to Agrotourism: An Innovative Strategy for Community Empowerment Programs in Martadinata Village - Nabila (Prospect Publishing, 2025)
Companies are key stakeholders with a fundamental role in the sustainable development of a nation. This role is realized through corporate social responsibility, one form of which is empowerment programs aimed at making a significant contribution to society. One company actively implementing empowerment programs in its operational areas is PT Pertamina Gas Operation Kalimantan Area. The company has launched several empowerment initiatives, including a local potential-based ecotourism program that has been running for the past two years in Martadinata Village, Kutai Timur Regency. However, this program appears to face certain limitations in its implementation. Adopting the triple bottom line approach, researchers have identified the potential for developing another local potential-based tourism program an agro-tourism initiative. This program can potentially broaden the impact of the existing ecotourism program and address various community issues simultaneously in Martadinata Village. The idea for this program stems from integrating the TAMAN Sidrap program, which is also an empowerment initiative by PT Pertamina Gas Operation Kalimantan Area, into an agro-tourism format. It is hoped that this program can serve as an effective option to maximize the benefits of existing programs, thereby improving the community's social, economic, and environmental quality of life.